Multi-instrument gravity-wave measurements over Tierra del Fuego and the Drake Passage – Part 1: Potential energies and vertical wavelengths from AIRS, COSMIC, HIRDLS, MLS-Aura, SAAMER, SABER and radiosondes - C. J. Wright; N. P. Hindley; A. C. Moss; N. J. Mitchell (Atmospheric Measurement Techniques, 2016)
Gravity waves in the terrestrial atmosphere are a vital geophysical process, acting to transport energy and momentum on a wide range of scales and to couple the various atmospheric layers. Despite the importance of these waves, the many studies to date have often exhibited very dissimilar results, and it remains unclear whether these differences are primarily instrumental or methodological. Here, we address this problem by comparing observations made by a diverse range of the most widely used gravity-wave-resolving instruments in a common geographic region around the southern Andes and Drake Passage, an area known to exhibit strong wave activity. Specifically, we use data from three limb-sounding radiometers (Microwave Limb Sounder, MLS-Aura; HIgh Resolution Dynamics Limb Sounder, HIRDLS; Sounding of the Atmosphere using Broadband Emission Radiometry, SABER), the Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) GPS-RO constellation, a ground-based meteor radar, the Advanced Infrared Sounder (AIRS) infrared nadir sounder and radiosondes to examine the gravity wave potential energy (GWPE) and vertical wavelengths ( λ z ) of individual gravity-wave packets from the lower troposphere to the edge of the lower thermosphere ( ∼ 100 km). Our results show important similarities and differences. Limb sounder measurements show high intercorrelation, typically > 0.80 between any instrument pair. Meteor radar observations agree in form with the limb sounders, despite vast technical differences. AIRS and radiosonde observations tend to be uncorrelated or anticorrelated with the other data sets, suggesting very different behaviour of the wave field in the different spectral regimes accessed by each instrument. Evidence of wave dissipation is seen, and varies strongly with season. Observed GWPE for individual wave packets exhibits a log-normal distribution, with short-timescale intermittency dominating over a well-repeated monthly-median seasonal cycle. GWPE and λ z exhibit strong correlations ...